Pengembangan Sistem Manajemen Skripsi Online Berbasis Web dengan Pelacakan Kemajuan Real-Time - Yusuf Muharam; Faisal Rizky; Sofy Nur Kholifah (Riau Jurnal Teknik Informatika, 2026)
Manual thesis supervision in higher education institutions generates recurring operational inefficiencies, including delayed document feedback, limited submission transparency, and the absence of centralized student progress monitoring. This study designs and implements a web-based thesis management system that digitalizes the complete academic supervision lifecycle using the Waterfall methodology for three user roles: Administrator, Supervisor, and Student. Functional testing across 47 black-box scenarios confirmed full compliance with all system requirements. User Acceptance Testing with 20 participants recorded 85% satisfaction at an average score of 4.25 out of 5.00. Post-implementation measurements revealed an 87.5% reduction in supervisor approval time, a 71.4% decrease in feedback response time, and a 95% improvement in examination scheduling efficiency, demonstrating the system's measurable impact on academic supervision processes at the Faculty of Information Technology, Universitas Bale Bandung